2019
DOI: 10.14710/nmjn.v8i2.20698
|View full text |Cite
|
Sign up to set email alerts
|

Behavior, Awareness and Sensitivity of Healthcare Providers in a Multicultural Environment

Abstract: Background:  The healthcare workforce of Saudi Arabia is characterized by diverse cultural backgrounds as a consequence of employment of expatriate workers from various countries. The heterogeneity of both providers of health services and clients resulted to cultural barriers that affected the delivery care.  It is paramount to evaluate the cultural competence of the healthcare providers (HCPs) to maintain quality holistic care. Objective: The primary objective of this study was to assess the cultural diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…However, important interventions should be undertaken to increase awareness and sensitivity when working with diverse patients [6]. A study by Hidayat and Musrifatul in 2019 found that the culture-based nursing care model is a culture-based approach model that plays an important role in overcoming children's health problems in the community, especially when cultural factors are conflicting with healthy principles [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, important interventions should be undertaken to increase awareness and sensitivity when working with diverse patients [6]. A study by Hidayat and Musrifatul in 2019 found that the culture-based nursing care model is a culture-based approach model that plays an important role in overcoming children's health problems in the community, especially when cultural factors are conflicting with healthy principles [7].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Russell Salvador in 2018 found that HCPs are very culturally competent, especially in changing aspects of behavior [6], [7]. The role of older mothers who are close to pregnant women may be relevant when conveying information.…”
Section: Discussionmentioning
confidence: 99%